To była miejscowość [...] rzeźników, krawców i szewców. Studium z historii rzemiosła i przemysłu w Grabowie - Chlebowska, Barbara (Zeszyty Wiejskie, 2016)
The paper is titled “It was a town of [...] tailors, shoemakers and butchers. A study on the history of crafts and industry in Grabów” is the chronicle of industrial enterprises and crafts in this town mainly in the interwar period and in the times of the Polish People’s Republic. The mill of Grabów was erected at the turn of the 19th and 20th centuries, and it originally belonged to a family of German settlers. The manor brickyard was built in the early 20th century. Both of these enterprises were nationalized after the World War II, and they have undergone numerous modernizations. The mill was returned to its pre-war owners and is still operating. In terms of crafts, Jewish tailors and shoemakers dominated the local market. In the period of the Polish People’s Republic, the structure of crafts was much more diversified.